Particle swarm modelling of a flexible beam structure - Mohamad, M.; Tokhi, M. O.; Toha, Siti Fauziah; Latiff, I. Abd. (2009)
This paper presents a particle swarm optimization (PSO) algorithm with dynamic spread factor inertia weight and its application to dynamic modeling of a flexible beam structure. In this study, system identification scheme based on PSO is formulated to obtain a dynamic model of the beam in parametric form. A PSO algorithm with dynamic spread factor inertia weight is proposed and its performance is assessed in comparison to a standard PSO in modelling the flexible beam structure.